A Comparative Study of Outside‐In and Inside‐Out Transobturator Tape Procedures for Female Stress Urinary Incontinence: 7‐Year Outcomes. Issue 3 (3rd March 2014) - CHUN, Ji‐Youn; SONG, Miho; YOO, Dae Seon; HAN, Ji‐Yeon; HONG, Bumsik; CHOO, Myung‐Soo
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to compare the long‐term surgical outcomes of the "inside‐out" (TVT‐O) and "outside‐in" (TOT) transobturator tape procedures for treating female stress urinary incontinence (SUI). Methods This was a retrospective analysis of women who underwent a transobturator tape procedure and were followed for at least 7 years. Patients' baseline characteristics and urodynamic parameters were compared between the two groups and analyzed to identify factors related to failure of therapy. Results A total of 215 patients were followed for > 7 years (TOT, n = 129; TVT‐O, n = 86), with a median follow‐up period of 7.1 years. No significant differences were observed in the baseline characteristics or urodynamic parameters between the groups, except incontinence type (TOT 33.3% vs. TVT‐O 52.3% with mixed urinary incontinence, P < 0.05). The TOT group had significantly higher cure rate, satisfaction with surgery, willingness to undergo the procedure to others, and willingness to receive the same procedure than those of the TVT‐O group (87.1 vs. 66.7%, 87.6 vs. 64.0%, 89.1 vs. 77.9%, and 77.5 vs. 57.0%, all P‐values < 0.05), respectively. A Univariate analysis identified maximum urethral closure pressure (MUCP) (odds ratio, 0.980; 95% confidence interval, 0.960–1.000; P = 0.046) as a risk factor for surgical failure. Conclusions TOT and TVT‐O procedures are safe and effective for the treatment of SUI in women over a 7‐year follow‐up period. The TOT procedure had higher cure rate and satisfaction rates than TVT‐O. MUCP may be associated with surgical outcome.